Back Cover: Integration of individual TiO2 nanotube on the chip: Nanodevice for hydrogen sensing (Phys. Status Solidi RRL 3/2015). Issue 3 (March 2015) - Enachi, Mihail; Lupan, Oleg; Braniste, Tudor; Sarua, Andrei; Chow, Lee; Mishra, Yogendra K.; Gedamu, Dawit; Adelung, Rainer; Tiginyanu, Ion
Abstract : No abstract is available for this article. Abstract : In their Letter on pp.171–174, Enachi et al. demonstrate, for the first time, a novel type of hydrogen sensors based on an individual TiO2 nanotube fabricated by anodic etching of titanium foils. As a result of comparative analysis of sensors consisting of amorphous (as‐grown), anatase (annealed at 450 °C) or mixed anatase/rutile (annealed at 650 °C) TiO2 structures, the authors found that the sensor based on single nanotube with mixed anatase/rutile structure shows the fastest response to hydrogen gas at room temperature. Along with this, the response for such structures is three times larger than that inherent to amorphous ones, and the recovery time is as low as 1–2 seconds. The obtained results pave the way for the use of individual TiO2 nanotubes in gas sensor applications, especially when small size and fast response have to be secured.